substitution method S-t=3 2S+3t=36
Answers
Answered by
9
Answer:
s= 9
t= 6
Step-by-step explanation:
t=s-3
put this into eq 2
2s+ 3(s-3)=36
2s + 3s -9 =36
5s = 36+9
5s = 45
s =9
then
put s=9 in eq 1
t = 9-3
t = 6
Answered by
5
Answer:
S=9 and t=6
Step-by-step explanation:
S-t=3-->1st equation
2S+3t=36-->2nd equation
S=3+t (from 1st equation)-->3rd equation
Substitute S=3+t in 2nd equation
2(3+t)+3t=36
6+2t+3t=36
2t+3t=36-6
5t=30
t=30/5
t=6
Substitute t=6 in 3rd equation
S=3+6
S=9
Similar questions